MOLECULAR DOCKING AND DYNAMIC SIMULATION-BASED SCREENING IDENTIFIES INHIBITORS OF TARGETED SARS-COV-2 3CLPRO AND HUMAN ACE2 - GALGALE, SARVESH; ZAINAB, RIDA; KUMAR A., PRADEEP; M., NITHYA; D., SUSHA; SHARMA, SAMEER (International Journal of Applied Pharmaceutics, 2023)
Objective: Several genetic variations of Severe Acute Respiratory Syndrome coronavirus-2 (SARS-CoV-2) are continuously arising due to the uncontrolled dissemination of the virus during the pandemic. Omicron (B.1.1.529), the most prevalent variation of concern, has demonstrated extraordinary proliferation and pathogenicity and has emerged as the dominant variant as it has inflicted mass casualties worldwide. Methods: Impeding the expression of 3CLpro, a coronavirus protease that is essential for digesting the RNA polyproteins, and the human angiotensin-converting enzyme 2 (ACE2) that serves as a receptor for the viral protein is identified as a competent therapeutic target. In the current study, human ACE2 and the viral 3CLpro complex was the target for the designing of novel drugs against the lethal virus. The docked complex was validated by Procheck, and the covid ligand library was investigated for its pharmacological efficacy using admetSAR 2.0. The molecular docking study was performed with the screened compounds obtained from the PubChem database against the docked protein complex. Results: The ACE2 and 3CLpro proteins were docked together and the best docked complex was utilized for the analysis of the 1,87,419 compounds retreived from the PubChem COVID library, 18,642 compunds fulfilled the pharmacological screening and were appraised for docking with ACE2-3CLpro complex. The molecular docking results presented that the compounds 1-(4-fluorophenyl)-N'-(4-methylphenyl)propane-1,3-diamine (CID: 10038137) demonstrated significantly better binding (-18.7 kacl/mol) with favourable pharmacological properties and was therefore subjected to molecular dynamic simulations using Desmond Schrodinger 2019.2 GPU enabled package for 100 ns trajectory. The complex structure was observed to be stable after 15 ns and the average RMSD was observed to be 0.65 nm. The complete binding energy of the complex with respect to MD simulation was-134.998+/-18.435 kj/mol which exposed that the inhibitor has a higher affinity towards the 3Clpro-ACE2 complex. Conclusion: Consequently, this compound can be used to develop anti-covid medications to combat complications associated with Omicron infection.